A parentalidade no contexto da guarda compartilhada. - Silva, Maria Lucia Cavalcanti de Mello e (2008)
This research had the objective to analyse the experience of parenthood by divorced and separated couples who chose joint custody to take care their children. The sample was intentional and compounded by six couples. Their are four couples (ex-husbands and ex-wives) and two incomplete couples (only one ex-husband and only a woman), as the total of ten people. The interviews were recorded, transcribed and submitted to Content Analyse. The themes were analysed as: how to choose this type of guard; how manage the parental responsabilities in this situation and what factors help or make difficult the maintenance of parental ties. The results showed that the choice by this type of guard was the oriented by a lawyer or other justice agent; regard the exercise of parental responsabilities, althought some difficulties, such as adjust the specificities this tie the respect and preserve the individuality by each member of the couple, the parents, in most cases, obtained sucess and took priority to children interests. The parental attributions were exercising in igualitarian type; the factors that help the parenthood maintenance in shared guard were: to priority the children well-being; to distinguish the conjugal ties to the parental ties; to maintain an open communication channel to deal with the children interests. The factors that difficult the joint custody were: a assimetric division of routine care, inapropriate communication between parents and their educational objectives and competition between them.